2023
DOI: 10.3390/biom13030439
|View full text |Cite
|
Sign up to set email alerts
|

BOX38, a DNA Marker for Selection of Essential Oil Yield of Rosa × rugosa

Abstract: Rosa rugosa L. was a famous aromatic plant whose cultivars (Rosa × rugosa) have been widely used in the perfume industry in Asia. The perfume market looks for rose cultivars bearing higher essential oil, while the oil yields of most R. × rugosa have not been evaluated due to limiting conditions, such as insufficient cultivation areas. Here, we tested the yield and the aroma components of essential oil of 19 R. × rugosa. The results indicated that the yields of nerol, citronellol, and geraniol could represent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Basic studies exploring the use of tissue-derived dECM in periodontal, [17] skeletal, [18] and cardiovascular [19] tissue engineering have also been extensively conducted. However, the application of tissue-derived dECM faces numerous challenges.…”
Section: Decmmentioning
confidence: 99%
“…Basic studies exploring the use of tissue-derived dECM in periodontal, [17] skeletal, [18] and cardiovascular [19] tissue engineering have also been extensively conducted. However, the application of tissue-derived dECM faces numerous challenges.…”
Section: Decmmentioning
confidence: 99%
“…Some of the cultivars, e.g., R. rugosa 'Fenghua' or R. rugosa 'Zizhi', have been wildly planted in different provinces of China for scented teas and essential oils [8,9]. The oil yields of these cultivars varied between 0.1 and 0.3% and identification of the high-oil-yield cultivars was important [9,10]. Although our previous study has identified eight high-oil-yield cultivars by a DNA marker of the cis-element [10], similar botanical characteristics among high-and low-oil-yield cultivars confuse farmers or breeders [2,11].…”
Section: Introductionmentioning
confidence: 99%
“…The oil yields of these cultivars varied between 0.1 and 0.3% and identification of the high-oil-yield cultivars was important [9,10]. Although our previous study has identified eight high-oil-yield cultivars by a DNA marker of the cis-element [10], similar botanical characteristics among high-and low-oil-yield cultivars confuse farmers or breeders [2,11]. It is necessary to construct a fingerprint of oil-bearing cultivars of R. rugosa based on DNA markers, not morphological markers.…”
Section: Introductionmentioning
confidence: 99%